SISTEM INFORMASI PENGELOLAAN KEUANGAN DI ORGANISASI SOLIDARITAS PEREMPUAN SEBAY LAMPUNG BERBASIS WEB - Machudor Yusman; Yohana Tri Utami; Febi Eka Febriansyah; Fitri Handayani (Jurnal Pepadun, 2022)
Financial administration in an organization is a financial management step that starts from acceptance to how the finances used are accounted for in an objective and systematic manner. The process of searching for financial data manually takes a very long time and a large error rate. This causes the vulnerability to lose data. Especially if the financial party requires data access that is done spontaneously, it will affect the speed level. In this study, a Financial Management Information System will be built that can be utilized by the relevant Section so that all Finance in the related section can be integrated into this system. The research method used in this study uses the waterfall method. This system is built using the Laravel Framework using the PHP language. This information system was built with the aim of providing fast, precise, accurate information regarding the required data and reports.